The Role of Biomulch Arachis pintoi In Increasing Soil Infiltration Rate on Sloping Land of Oil Palm Plantation - Sarjono, Arif; Guntoro, Dwi; Supijatno, Supijatno (Department of Agronomy and Horticulture, IPB University, 2018)
The slope of land in oil palm plantation areas is the one of the primary causes of low soil water content due to low rates of soil infiltration. Biomulch is one of the conservation methods that can be used to cover and shield the soil from weeds, prevent soil erosion, and increase the rate of soil infiltration. Arachis pintoi is a perennial, stoloniferous legume crop that has potentials to be used as biomulch. The objective of the research was to study the role of Arachis pintoi in increasing the rate of soil infiltration on a sloping land of oil palm plantation. The research was conducted on the slope land (22.8%) of the Bukit Kemuning Farmer Group, Mersam, Batanghari, Jambi, Indonesia (01036'21